The Cognitive Association Between Effortful Self-Control and Decreased Vitality - Bertrams, Alex (Frontiers in Psychology, 2021)
According to the schema model of self-control, individuals’ self-control efforts activate the fatigue/decreased vitality schema. A precondition for this schema activation is that the cognitive concepts of self-control effort and decreased vitality are associated in individuals’ minds. In the present two studies, the existence of such a cognitive association was tested. In Study 1, 133 school students from Switzerland read two similar stories in a random order. In one story, a fictitious individual engaged in effortful self-control, while in the other story, he/she did not. In Study 2, 251 online workers from the United States, per random assignment, received either a story describing an individual exerting self-control or a similar story describing an individual not exerting self-control. In both studies, the participants rated how vital the fictitious individuals felt at the time the story ended. As expected, in both studies, the fictitious individual exerting self-control was rated as feeling less vital compared to the one not exerting self-control. This finding is in line with the schema model of self-control, as it indicates that the concepts of self-control exertion and decreased vitality are related to each other in a cognitive associative structure. Additional results suggest that emotional valence and calmness are irrelevant in this association. Moreover, the self-control exertion–decreased vitality association was independent from the raters’ own momentary feelings of self-control exertion, effort, and exhaustion.